PENINGKATAN KEMAMPUAN MENGENAL ANGKA MELALUI PEMANFAATAN BAHAN SISA SEBAGAI MEDIA PEMBELAJARAN PADA ANAK USIA DINI DI TAMAN KANAK-KANAK PERTIWI KATIALO SOLOK - Asmawati Asmawati; Rismareni Pransiska (Universitas Islam Yasni Bungo, 2026)
This study aimed to improve early childhood numeracy recognition skills through the utilization of recycled materials at TK Pertiwi Katialo Solok. Number recognition ability is an important aspect of children’s cognitive development and serves as the foundation for learning mathematics at higher educational levels. Based on the preliminary observation, most children in Group B still experienced difficulties in mentioning numbers sequentially, recognizing number symbols, arranging numbers in order, and matching numbers with the quantity of objects. This research employed the Classroom Action Research (CAR) method conducted in two cycles, where each cycle consisted of planning, action implementation, observation, and reflection stages. The research subjects were 15 children consisting of 7 boys and 8 girls. Data collection techniques included observation, documentation, and performance assessment. The data were analyzed descriptively using qualitative and quantitative approaches through success percentage analysis. The results showed that the use of recycled materials such as used cardboard, bottle caps, straws, and waste paper significantly improved children’s number recognition skills. In the initial condition, only 33% of children achieved the expected developmental category. In Cycle I, the percentage increased to 60%, and in Cycle II, it increased to 87%. The children became more active, enthusiastic, and able to understand number concepts more easily because learning activities were conducted through concrete and enjoyable play-based activities. Therefore, the utilization of recycled materials proved to be effective in improving number recognition skills among early childhood students at TK Pertiwi Katialo Solok.